1987
DOI: 10.1002/cne.902570407
|View full text |Cite
|
Sign up to set email alerts
|

An ultrastructural analysis of the sympathetic neuromuscular junctions on arterioles of the submucosa of the guinea pig ileum

Abstract: The relationship of the varicosities of sympathetic postganglionic nerve terminals to the smooth muscle cells of arterioles in the submucosa of the guinea pig ileum has been investigated quantitatively by electron microscopy. Longitudinal sections were cut through arterioles about 50 micron in diameter after fixation in vitro or in situ under pressure. About 13% of the varicosities in individual ultrathin sections made contact with the outer surface of the smooth muscle cells. The neuromuscular junctions resem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 32 publications
4
54
0
Order By: Relevance
“…Instead some investigators have suggested that transmitter is released en passage as action potentials conduct down axons, and innervation is defined by the volume through which a transmitter can diffuse and still reach postjunctional receptors at an effective concentration. This concept has been challenged by recent studies using serialsectioning techniques and electron microscopy that have shown that distinct neuromuscular junctions are present in autonomically innervated tissues; however the structure of these junctions is less well defined than is that of skeletal neuromuscular junctions (Luff et al, 1987;Gabella, 1995). The present study suggests that close contacts between motor neurons and postjunctional cells are an important feature of enteric neurotransmission.…”
Section: Discussionmentioning
confidence: 59%
“…Instead some investigators have suggested that transmitter is released en passage as action potentials conduct down axons, and innervation is defined by the volume through which a transmitter can diffuse and still reach postjunctional receptors at an effective concentration. This concept has been challenged by recent studies using serialsectioning techniques and electron microscopy that have shown that distinct neuromuscular junctions are present in autonomically innervated tissues; however the structure of these junctions is less well defined than is that of skeletal neuromuscular junctions (Luff et al, 1987;Gabella, 1995). The present study suggests that close contacts between motor neurons and postjunctional cells are an important feature of enteric neurotransmission.…”
Section: Discussionmentioning
confidence: 59%
“…However, it is not known how many release sites occur in each of these varicosities. Many varicosities on arterioles come into close apposition to smooth muscle cells, with only basal lamina intervening between the two structures (Luff, McLachlan & Hirst, 1987). Some varicosities which come into close apposition with smooth muscle cells show no prejunctional specializations while most show one specialization (Luff & McLachlan, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…It is not known where cholinergic nerves terminate and release ACh in the ACh FROM NER VES ACTIVATES ENDOTHELIUM vasculature, but it is presumably in the adventitial layer of the arteriole as is the case for sympathetic neurotransmitter release because no nerve fibres or axon varicosities exist in the arteriolar smooth muscular or endothelial layer (Luff, McLachlan & Hirst, 1987;Hirst, 1989). Indeed, it seems quite possible that ACh is released from distances more extraluminal than the adventitially located sympathetic nerve terminals in view of the electron microscopic evidence presented by Luff et al (1987) that the vast majority of axon varicosities in the adventitia of submucosal arterioles are sympathetic.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it seems quite possible that ACh is released from distances more extraluminal than the adventitially located sympathetic nerve terminals in view of the electron microscopic evidence presented by Luff et al (1987) that the vast majority of axon varicosities in the adventitia of submucosal arterioles are sympathetic. Now that it is possible to directly identify a single vasodilator neurone by intracellular stimulation of the cell body and simultaneous recording of vessel diameter (see Neild et al 1990), combining intracellular dye injections with subsequent light and electron microscopic examinations should soon provide detailed information concerning the distance between vascular ACh release sites and muscarinic receptors on endothelial cells.…”
Section: Discussionmentioning
confidence: 99%